GAMM Annual Meeting – Kassel 2020 Overview of the Sections (Proceedings in applied mathematics and mechanics, 2021)
Volume 20 (2020), Issue 1 of PAMM “Proceedings in Applied Mathematics and Mechanics” assembles the contributions to the 91st Annual Meeting of the Gesellschaft für Angewandte Mathematik und Mechanik (GAMM), organized in 2020 by Universität Kassel, Germany, and held as a virtual conference. The contributions are grouped according to the minisymposia and sessions of the conference. Overview of the Sections GAMM related DFG Priority Programmes DFG‐PP 1748 Reliable Simulation Techniques in Solid Mechanics. Development of Non‐Standard Discretization Methods, Mechanical and Mathematical Analysis DFG‐PP 1881 Turbulent Superstructure DFG‐PP 1886 Polymorphic Uncertainty Modelling for the Numerical Design of Structures DFG‐PP 1897 Calm, Smooth and Smart – Novel Approaches for Influencing Vibrations by Means of Deliberately Introduced Dissipation DFG‐PP 2020 Cyclic Deterioration of High‐Performance Concrete in an Experimental‐Virtual Lab Minisymposia MS 1 Computational Photonics MS 3 Dissipativity, turnpikes and optimal control MS 4 Advanced experimental and computational techniques in polymer mechanics Sections 1–24 S1 Multi‐body dynamics S2 Biomechanics S3 Damage and fracture mechanics S4 Structural mechanics S5 Nonlinear oscillations S6 Material modelling in solid mechanics S7 Coupled problems S8 Multiscales and homogenization S9 Laminar flows and transition S10 Turbulence and reactive flows S11 Interfacial flows S12 Waves and acoustics S13 Flow control S14 Applied analysis S15 Uncertainty quantification S16 Optimization S17 Applied and numerical linear algebra S18 Numerical methods of differential equations S19 Optimization of differential equations S20 Dynamics and control S21 Mathematical signal and image processing S22 Scientific computing S24 History of mechanics Young Researchers' Minisymposia YRM1 Algorithms for coupled multi‐physics problems YRM2 Rank structured matrix and tensor techniques YRM6 Novel discretization methods for phase‐field modeling in fracture mechanics